The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/publications10010010
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Collaboration Patterns in Computer Science

Abstract: The research discipline of computer science (CS) has a well-publicized gender disparity. Multiple studies estimate the ratio of women among publishing researchers to be around 15–30%. Many explanatory factors have been studied in association with this gender gap, including differences in collaboration patterns. Here, we extend this body of knowledge by looking at differences in collaboration patterns specific to various fields and subfields of CS. We curated a dataset of nearly 20,000 unique authors of some 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…For the remaining 3,331 authors, we looked up genders manually on the web as we have with systems conferences, leaving only 162 people for which we could not assign a gender manually or automatically. The overall gender statistics for these conferences are shown in Table 2 , and the full details on this auxiliary dataset are available in the original study of that data [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the remaining 3,331 authors, we looked up genders manually on the web as we have with systems conferences, leaving only 162 people for which we could not assign a gender manually or automatically. The overall gender statistics for these conferences are shown in Table 2 , and the full details on this auxiliary dataset are available in the original study of that data [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, men develop significantly larger networks, even when controlling for time variables such as the year or seniority, though with small effect size. In a recent descriptive analysis of major conferences in computer systems in 2017 (Yamamoto and Frachtenberg, 2022 ), men were shown to have more coauthors per paper and overall than women, but the difference was rather small. An analysis of four Italian conferences in the fields of information systems and computer science revealed that “men are more key than women” in only one of the four considered communities.…”
Section: Related Workmentioning
confidence: 99%
“…As shown by Sarsons et al ( 2021 ), female and male economists who write most of their papers alone have similar tenure rates, conditional on the quality of their contributions. Existing studies on sole authorship seem to agree that women write a smaller proportion of their publications alone (West et al, 2013 ; Ductor et al, 2018 ; Sarsons et al, 2021 ; Yamamoto and Frachtenberg, 2022 ). In one of the few works addressing the question of gender and solo research in more detail, however, Kwiek and Roszka ( 2022 ) find only marginal gender differences among researchers at Polish universities.…”
Section: Related Workmentioning
confidence: 99%
“…The complete methodological aspects of identifying and cleaning the appropriate data as well as the main statistical findings about the underrepresentation of women in the field can be found in our original study. 1 Here, we combine our current dataset with prior studies to try to evaluate the impact of each of the 10 potential factors on the increased gender gap in systems, each presented as a hypothesis that it has a more significant effect on the gender gap in systems in particular. The 10 hypotheses are organized into two groups: six where our data provide evidence for or against an increased effect and four for which we have no specific data but can speculate based on the characteristics of systems research.…”
Section: Notes From the Fieldmentioning
confidence: 99%
“…
In a recent study, we found that the ratio of femaleto-male authors in computer systems conferences is particularly low, even compared to the rest of computer science (CS). 1 The large and statistically significant underrepresentation cannot be fully explained by review bias, differences in collaboration patterns, and numerous other demographic and conference factors alone. 2
…”
mentioning
confidence: 99%